Exchange Market Pressure in Indonesia: A Univariate Markov Switching Analysis - Heriqbaldi, Unggul (Asian Economic and Financial Review, 2012)
The aim of this paper is to analyze the nature of exchange market pressure in the case of the Indonesian economy. More specifically, this paper aims to answer whether there is non-linearity or multiple equilibria in the EMPI. The paper relies on a univariate Markov Switching autoregressive model. The model estimation also incorporates procedures such as unit root test, diagnostic test and log likelihood ratio test, focusing on the period from January 1990 to September 2008. This paper found that a 2-state Markov switching AR(6) model of EMPI outperforms a linear autoregressive model in explaining the behavior of EMPI. The findings also suggest that the significant regime dependent intercept confirms the existence of a multiple-equilibria condition in the EMPI. The degree of uncertainty of EMPI in a volatile state was found to be much higher than in the stable state and there was also an inertia characteristic. Due to the inertia characteristic in the EMPI, the monetary authority should take into account the role of economic agents’ expectations in delivering monetary policy to stabilize the exchange rate following significant market pressure in the economy. This paper contributes by providing empirical evidence on the characteristics of EMPI in the context of the Indonesian economy.